MONOLITHIC PURE CENTER PIEZOELECTRIC ROTARY PLATFORM WITHOUT ACTUATOR REDUNDANCY - WU YuXi; YANG YiLing; WU GaoHua; DU HuiLin; WEI YanDing (Jixie qiangdu)
In order to achieve high⁃precision and pure⁃center rotation motion in micro/nanomanipulation tasks,a monolithic pure⁃center rotation platform was designed using two⁃stage compliant amplification mechanisms and a single piezoelectric actuator.Compared with other platforms,the designed rotation platform exhibited the merits of no actuator redundancy,high natural frequency,large rotation angle,and compact structure.The static and dynamic models were established by combining the pseudo⁃rigid body and finite element methods.Also,the output angle,input stiffness,output stiffness,and natural frequency of the rotation platform were simulated by Ansys software.Finally,an experimental test system was built,and the performance of the platform was tested through several experiments.Also,the feedforward control was used to compensate for the piezoelectric hysteresis.The experimental results show that the rotation angle is 16.8 mrad,the natural frequency is 527.3 Hz,and the resolution is 0.3μrad.Meanwhile,the hysteresis nonlinearity is compensated effectively using feedforward control.Thus,the platform is capable the high precision center rotation operation.